2019
DOI: 10.1002/pssb.201800570
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Elastic, Mechanical and Electronic Properties of NbW‐Based Intermetallic Compounds: First‐Principles Calculations

Abstract: The structural, elastic and electronic properties of NbW‐based intermetallic compounds have been investigated by first‐principles calculations from CASTEP code based on density functional theory (DFT). The calculated lattice parameters of NbW‐based intermetallic compounds are in good agreement with the experimental values. The calculated elastic constants indicate that NbW, CNb0.8W0.2, Mo0.333Nb0.333W0.333, Nb0.33Ta0.33W0.34, Nb0.75Se2W0.25, and Nb2.25S6W0.75 have mechanically stable structures. The bulk modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It was observed that the Ga-4s orbitals hybridizes strongly with those of Cu-3d and S-3p, and the impurity states appear above the E F (see Figure S4, Supporting Information), which is also observed in Cu 11.5 Ge 0.5 Sb 4 S 13 and Cu 11.5 Sn 0.5 Sb 4 S 13 system. [33] The presence of impurity states can hinder the carrier transport from VB to CB, due to the annihilation between the electrons and holes. In this regard, the electrical conductivity [48] The band structures with different Te content incorporation are presented in Figure 5b, where the lowering of the CB is observed when the Te atom number increases from 1 to 4, which narrows the bandgap.…”
Section: Band Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the Ga-4s orbitals hybridizes strongly with those of Cu-3d and S-3p, and the impurity states appear above the E F (see Figure S4, Supporting Information), which is also observed in Cu 11.5 Ge 0.5 Sb 4 S 13 and Cu 11.5 Sn 0.5 Sb 4 S 13 system. [33] The presence of impurity states can hinder the carrier transport from VB to CB, due to the annihilation between the electrons and holes. In this regard, the electrical conductivity [48] The band structures with different Te content incorporation are presented in Figure 5b, where the lowering of the CB is observed when the Te atom number increases from 1 to 4, which narrows the bandgap.…”
Section: Band Structuresmentioning
confidence: 99%
“…[27] Its estimated carrier concentration is above 3 Â 10 21 cm À3 , which is a very high compared to the optimum concentrations (10 19 -10 20 cm À3 ). [28] In previous studies, many strategies involving the chemical elements doping were proposed to tune the electronic transport [23][24][25][26][27][28][29][30][31][32][33][34][35][36] and at the same time, reduce the thermal transport properties. For instance, the ZT value of Cu 12Àx M x Sb 4 S 13 (M is Ge or Sn, x = 0.3-0.5) increases from ≈0.46 to ≈0.65 at 665 K. But because the PF decreases, only a slight improvement in ZT value is achieved.…”
Section: Introductionmentioning
confidence: 99%